Electrochemical Dehydrogenative C(sp(2))−H Amination - Puthanveedu, Mahesh (Chemistry, 2021)
A transition‐metal‐free direct electrolytic C−H amination involving an electrochemically generated nitrenium ion intermediate has been developed. The electrosynthesis takes place in the absence of any organoiodine catalysts and is enabled by an in situ generated electrolyte. A novel, efficient intramolecular and intermolecular C−H amination has been demonstrated using a simple reaction setup.